Penyuluhan Kesehatan Tentang Makanan Sehat Bagi Penderita Hipertensi pada Lansia di Desa Labuhan Labo Kota Padangsidimpuan Tahun 2018 - Ramadhini, Delfi; Ritonga, Nefonafratilova (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Hypertension or high blood pressure is a symptom of an increase in a person's blood pressure above normal which results in the supply of oxygen and nutrients carried by the blood being blocked to the tissues of the body that need it. Based on WHO data, it is estimated that there are 600 million people with hypertension worldwide, with 3 million deaths each year. Hypertension is also in the 2nd rank of 10 most diseases in outpatients in hospitals in Indonesia in 2006 with a prevalence of 4.67%. The purpose of this PKM is to motivate the elderly about the importance of knowing healthy food, foods that can and should not be consumed by people with hypertension so that the elderly can continue to maintain health. PKM activities are carried out by means of health education methods using slide show powerpoint media and posters to elderly people with hypertension in the village of Labuan Labo totaling 50 people. The results of this counseling activity were continued by providing an evaluation to elderly people with hypertension, namely questions and answers about the material provided. There are three questions given by the extension agent to elderly people with hypertension. Based on the answers given, it shows that elderly people with hypertension understand the material provided by the extension agents, although there are elderly people who have difficulty remembering. PKM activities carried out went well. Elderly people with hypertension who participated in the activity seemed enthusiastic about participating in the counseling activities. Hypertension or high blood pressure is a symptom of an increase in a person's blood pressure above normal which results in the supply of oxygen and nutrients carried by the blood being blocked to the tissues of the body that need it. Based on WHO data, it is estimated that there are 600 million people with hypertension worldwide, with 3 million deaths each year. Hypertension is also in the 2nd rank of 10 most diseases in outpatients in hospitals in Indonesia in 2006 with a prevalence of 4.67%. The purpose of this PKM is to motivate the elderly about the importance of knowing healthy food, foods that can and should not be consumed by people with hypertension so that the elderly can continue to maintain health. PKM activities are carried out by means of health education methods using slide show powerpoint media and posters to elderly people with hypertension in the village of Labuan Labo totaling 50 people. The results of this counseling activity were continued by providing an evaluation to elderly people with hypertension, namely questions and answers about the material provided. There are three questions given by the extension agent to elderly people with hypertension. Based on the answers given, it shows that elderly people with hypertension understand the material provided by the extension agents, although there are elderly people who have difficulty remembering. PKM activities carried out went well. Elderly people with hypertension who participated in the activity seemed enthusiastic about participating in the counseling activities.